CHOS gas/fluid‐induced reduction in ureilites. (28th October 2021) - Langendam, Andrew D.; Tomkins, Andrew G.; Evans, Katy A.; Wilson, Nicholas C.; M Rae, Colin M.; Stephen, Natasha R.; Torpy, Aaron
Abstract: Ureilite meteorites contain regions of localized olivine reduction to Fe metal widely accepted to have formed by redox reactions involving oxidation of graphite, a process known as secondary smelting. However, the possibility that other reductants might be responsible for this process has largely been ignored. Here, 17 ureilite samples are investigated to assess whether, instead of smelting involving only solid reactants, a CHOS gas/fluid could have caused much of the smelting. Features consistent with gas‐ or supercritical fluid‐driven reduction were found to be abundant in all ureilites, such as fracture‐focused smelting, plume‐like reaction fronts, and addition of sulfur. Many of these are developed away from graphite. In some ureilites, it is clear that the redox process coincided with annealing, and we suggest that this was caused by enhanced diffusion facilitated by a higher density gas or fluid, rather than slow cooling, which requires elevated pressure. The C‐CO and CH4 ‐C‐H2 O buffers were modeled to examine their relative potential to drive reduction. This modeling showed that a CH4 ‐rich fluid is able to produce the observed mineral compositions at elevated pressures. This result, coupled with the observed textures, is used to develop a likely series of reactions. We suggest that at higher pressures, a H2 ‐CH4 ‐H2 S‐S2 ‐bearing fluid‐like phase, and at lower pressures, an equivalent gas, were able to infiltrate grain boundaries and fine fractures. Sulfidation to form troilite may have acted to maintain highly reduced gas/fluid conditions. The presence of hydrocarbons in ureilites supports a role for reduction driven by CHOS gas/fluid.